Solid oxide fuel cell and method for manufacturing solid oxide fuel cell

By enhancing the wettability of the inner frame surface in solid oxide fuel cells, the design effectively prevents gas leakage and maintains sealing integrity at high temperatures, addressing the challenges of porosity and sealing material impairment.

JP2025069776APending Publication Date: 2025-05-01NISSAN MOTOR CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023179707
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-05-01

AI Technical Summary

Technical Problem

Solid oxide fuel cells face challenges with gas leakage due to the porosity of the metal support layer, which can lead to gas mixing between electrodes, and the sealing properties of glass sealing materials may be impaired at high temperatures.

Method used

The solid oxide fuel cell design includes a frame with improved wettability on the inner surface for the glass sealing material, which attracts and retains the sealing material even at high temperatures, preventing gas leakage and maintaining sealing integrity.

Benefits of technology

This design effectively prevents the glass sealing material from flowing and impairing sealing properties, ensuring efficient gas separation and power generation in solid oxide fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025069776000001_ABST
    Figure 2025069776000001_ABST
Patent Text Reader

Abstract

To prevent loss of sealing performance due to flow of a glass sealant.SOLUTION: A solid oxide fuel cell 100 includes a battery cell 10 having a porous metal support 2, a first electrode layer 3 laminated on the metal support 2, an electrolyte layer 4 laminated on the first electrode layer 3, and a second electrode layer 5 laminated on the electrolyte layer 4, and a frame 6 that holds the battery cell 10. An end face 8 of the battery cell 10 and the frame 6 are joined by a glass sealant 7. The frame 6 has an inner frame surface 6b in contact with the glass sealant 7 with better wettability than an outer frame surface 6c located outside the glass sealant 7.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid oxide fuel cell and a method for producing a solid oxide fuel cell. [Background technology]

[0002] A solid oxide fuel cell is a fuel cell that uses a solid material as an electrolyte. A solid oxide fuel cell usually has an electrolyte layer, an anode electrode, and a cathode electrode. The anode electrode and the cathode electrode are arranged so as to sandwich the electrolyte layer. During power generation, an anode gas is supplied to the anode electrode, and a cathode gas is supplied to the cathode electrode. A metal support layer may be provided on the outside of the anode electrode and / or the cathode electrode as a support material. The metal support layer needs to have gas permeability so that gas from the outside can be supplied to the electrode. Therefore, the metal support layer is usually formed of a porous material.

[0003] Since the metal support layer is porous, the supplied gas may leak from the edge of the metal support layer. As a result, the gas may mix between the two electrodes. To achieve efficient power generation, it is necessary to prevent the gas from leaking from the edge so that the gas is separated between the two electrodes.

[0004] In relation to the above, Patent Document 1 discloses a solid oxide fuel cell comprising a fuel cell and a frame arranged around the fuel cell, in which the fuel cell and the frame are joined via a sealing material (glass sealing material) containing glass. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2016-207630 A Summary of the Invention [Problem to be solved by the invention]

[0006] According to the technology described in Patent Document 1, gas leakage is prevented by a glass sealant. However, solid oxide fuel cells can reach high temperatures during operation. As a result, if the glass sealant softens and flows, the sealing performance may be impaired.

[0007] The present invention has been made in view of the above technical problems, and has an object to prevent the glass sealant from flowing and losing its sealing properties. [Means for solving the problem]

[0008] According to one embodiment of the present invention, a solid oxide fuel cell includes a porous metal support, a battery cell having a first electrode layer laminated on the metal support, an electrolyte layer laminated on the first electrode layer, and a second electrode layer laminated on the electrolyte layer, and a frame that holds the battery cell. An end face of the battery cell and the frame are joined with a glass sealant. The frame has an inner frame surface that contacts the glass sealant with better wettability than an outer frame surface located outside the glass sealant. Effect of the Invention

[0009] According to the above aspect, even if the solid oxide fuel cell becomes hot and the glass sealant softens, the glass sealant is attracted to the inner frame surface, which has better wettability than the outer frame surface. In other words, the glass sealant is prevented from flowing in a direction away from the battery cell. This prevents the glass sealant from flowing and losing its sealing ability. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a top view of a solid oxide fuel cell according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view taken along line II-II in FIG. [Diagram 3] FIG. 3 is a top view of the frame. [Figure 4] FIG. 4 is a flowchart showing the procedure for manufacturing a solid oxide fuel cell. [Diagram 5] FIG. 5 is a schematic cross-sectional view of a solid oxide fuel cell according to a second embodiment of the present invention. [Figure 6] FIG. 6 is a schematic cross-sectional view of a solid oxide fuel cell according to a third embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] First Embodiment A solid oxide fuel cell 100 according to a first embodiment of the present invention will now be described with reference to the accompanying drawings.

[0012] Fig. 1 is a view of a solid oxide fuel cell 100 viewed along the stacking direction of the fuel cells 10. That is, Fig. 1 is a top view of the solid oxide fuel cell 100. Fig. 2 is a schematic cross-sectional view taken along line II-II in Fig. 1. Fig. 3 is a top view of a frame 6.

[0013] As shown in Figures 1 and 2, a solid oxide fuel cell 100 generally comprises a battery cell 10, a frame 6 that holds the battery cell 10, and a glass sealant 7 that joins the battery cell 10 and the frame 6.

[0014] The battery cell 10 has a porous metal support 2, a first electrode layer 3, an electrolyte layer 4, and a second electrode layer 5. These are laminated. That is, the first electrode layer 3 is laminated on the metal support 2, the electrolyte layer 4 is laminated on the first electrode layer 3, and the second electrode layer 5 is laminated on the electrolyte layer 4. In other words, the electrolyte layer 4 is sandwiched between the first electrode layer 3 and the second electrode layer 5.

[0015] One of the first electrode layer 3 and the second electrode layer 5 functions as an anode, and the other functions as a cathode. The first electrode layer 3 may be the anode, or the second electrode layer 5 may be the anode. When the solid oxide fuel cell 100 is in operation, an anode gas is supplied to one of the first electrode layer 3 and the second electrode layer 5, and a cathode gas is supplied to the other. As an example, the first electrode layer 3 can be used as a fuel electrode layer (anode), and the second electrode layer 5 can be used as an air electrode layer (cathode).

[0016] The battery cells 10 are supported on the metal support body 2 side by a metal frame 6. Specifically, the outer periphery of the metal support body 2 is positioned on the rim of the frame 6. The battery cells 10 are joined to the frame 6 at this outer periphery by welding.

[0017] In addition, the center of the lower surface (the surface bonded to the frame 6) of the metal support 2 is located above the opening 6a of the frame 6. That is, the lower surface of the metal support 2 is exposed at the center. With this configuration, it is possible to supply gas (anode gas or cathode gas) to the first electrode layer 3 through the porous metal support 2.

[0018] The electrolyte layer 4 is formed of a dense ceramic layer. The term "ceramics" refers to a sintered body of an inorganic material, and is a concept that includes not only nonmetallic oxides but also metal oxides. The electrolyte layer 4 may be configured to be capable of conducting oxide ions while not allowing gas to pass through. For example, the electrolyte layer 4 may be formed of a solid oxide ceramic. The solid oxide ceramic is not particularly limited, but may be, for example, a zirconia-containing material. The zirconia-containing material may be, for example, stabilized zirconia doped with yttrium, samarium, gadolinium, scandium, or the like. The thickness of the electrolyte layer 4 is, for example, 0.5 to 20 μm, preferably 1 to 10 μm.

[0019] The metal support 2, the first electrode layer 3, and the second electrode layer 5 each have a porous structure. The first electrode layer 3 and the second electrode layer 5 are provided so as to sandwich the electrolyte layer 4, and are joined to the electrolyte layer 4. The metal support 2 is provided on the outer side (lower side in FIG. 2) of the first electrode layer 3. Another metal support may be provided on the outer side (upper side in FIG. 2) of the second electrode layer 5.

[0020] The first electrode layer 3 and the second electrode layer 5 are layers through which electrons are exchanged during power generation. The first electrode layer 3 and the second electrode layer 5 are made of porous ceramic layers. The porous ceramic layers can be formed, for example, of a mixture (cermet) of solid oxide ceramics and a metal element having catalytic activity, or of solid oxide ceramics on which a metal element having catalytic activity is supported by an impregnation method, or of electronic and ionic mixed conductive ceramics. Examples of solid oxide ceramics include stabilized zirconia doped with yttrium, samarium, gadolinium, scandium, etc. Examples of metal elements having catalytic activity include precious metal materials such as platinum, nickel, and praseodymium. Examples of electronic and ionic mixed conductive ceramics include lanthanum cobaltite doped with strontium, iron, etc. The thickness of each of the first electrode layer 3 and the second electrode layer 5 is, for example, 0.3 to 50 μm, preferably 0.5 to 30 μm.

[0021] In this embodiment, the second electrode layer 5 is formed smaller than the electrolyte layer 4. That is, when viewed along the stacking direction of the battery cell 10, the outer shape of the second electrode layer 5 is located inside the outer shape of the electrolyte layer 4. This makes it difficult for the first electrode layer 3 and the second electrode layer 5 to be short-circuited. However, the second electrode layer 5 may be formed to be the same size as the electrolyte layer 4. Also, when viewed along the stacking direction, a part of the outer shape of the second electrode layer 5 may match the outer shape of the electrolyte layer 4.

[0022] The metal support 2 is made of a porous metal. The metal support 2 is provided for the purpose of shape retention and the like. By providing the metal support 2, the shape is maintained even when the electrolyte layer 4, the first electrode layer 3, and the second electrode layer 5 are thin. The thickness of the metal support 2 is determined from the viewpoint of shape retention and is, for example, 50 to 1000 μm, preferably 100 to 500 μm. The metal support 2 can be formed from, for example, Fe and Cr. As an example, the metal support 2 can be made of SUS.

[0023] The glass sealant 7 is provided so as to cover the end surface 8 of the battery cell 10. As described above, the metal support 2 and the first electrode layer 3 are porous. Therefore, the glass sealant 7 is provided to prevent gas supplied to the metal support 2 and the first electrode layer 3 from leaking from the end surface 8 of the battery cell 10.

[0024] The sealing properties can be ensured as long as at least the metal support 2 and the first electrode layer 3 are covered with the glass sealant 7. In other words, "covering the end face 8 of the battery cell 10" means that at least the metal support 2 and the first electrode layer 3 are covered. The glass sealant 7 may be provided so as to cover up to the upper surface of the end of the electrolyte layer 4.

[0025] The glass seal material 7 is required to have insulating properties and a gas blocking function. The glass seal material 7 may be a material containing Si as a main component and containing an alkali or alkaline earth metal as another component.

[0026] The solid oxide fuel cell 100 may reach high temperatures during operation, which may cause the glass sealant 7 to soften and flow, potentially compromising the sealing performance.

[0027] In contrast, in the solid oxide fuel cell 100 of this embodiment, the wettability of the inner frame surface 6b (see Figures 2 and 3) that comes into contact with the glass sealant 7 is made better than the wettability of the outer frame surface 6c (see Figures 2 and 3) that is located outside the glass sealant 7.

[0028] As a result, even if the solid oxide fuel cell 100 becomes hot and the glass sealant 7 softens, the glass sealant 7 is attracted to the inner frame surface 6b, which has better wettability than the outer frame surface 6c. In other words, the glass sealant 7 is prevented from flowing in a direction away from the battery cells 10. This prevents the glass sealant 7 from flowing and being damaged.

[0029] The state in which the wettability of the inner frame surface 6b is better than that of the outer frame surface 6c may be achieved by reducing the wettability of the outer frame surface 6c, or by improving the wettability of the inner frame surface 6b, or both may be adopted.

[0030] As an example, in this embodiment, as shown in an enlarged view in Fig. 2, the surface roughness of the outer peripheral frame surface 6c is relatively larger than that of the inner peripheral frame surface 6b. This may be achieved by making the surface roughness of the outer peripheral frame surface 6c larger than that of the inner peripheral frame surface 6b, or by making the surface roughness of the inner peripheral frame surface 6b smaller than that of the outer peripheral frame surface 6c. The greater the surface roughness, the larger the contact angle of the glass seal material 7. In other words, the greater the surface roughness, the lower the wettability.

[0031] Examples of methods for making the surface roughness of the outer peripheral frame surface 6c greater than that of the inner peripheral frame surface 6b include roughening processes such as cutting and honing. The surface roughness of the outer peripheral frame surface 6c can also be increased by applying a material addition process such as plating or spraying. Examples of materials added in the material addition process include precious metals such as gold and silver. In addition, the wettability of the outer peripheral frame surface 6c can be reduced by adding a material that has a low affinity with the glass sealant 7 in the material addition process.

[0032] Furthermore, if the frame 6 is covered with an oxide film, the wettability of the outer peripheral frame surface 6c can be reduced by performing an oxide film removal process to remove the oxide film. Since the oxide film has a high affinity with the glass seal material 7, removing the oxide film reduces the wettability. For example, if the frame 6 is made of stainless steel, removing the oxide film to expose the metal surface can reduce the wettability of the outer peripheral frame surface 6c.

[0033] A method for reducing the surface roughness of the inner frame surface 6b includes, for example, a smoothing process such as polishing. The surface roughness of the inner frame surface 6b can also be reduced by performing a material addition process such as plating or spraying. The wettability of the inner frame surface 6b can also be improved by adding a material that has a high affinity with the glass seal material 7 through the material addition process. Examples of materials that have a high affinity with the glass seal material 7 include components contained in the glass seal material 7. For example, these are Si and oxide materials.

[0034] In addition, if the frame 6 is not covered with an oxide film, the wettability of the inner frame surface 6b can be improved by performing an oxide film forming process to form an oxide film, such as a high-temperature heat treatment in an oxidizing atmosphere or a plasma deposition process.

[0035] The inner frame surface 6b may be expanded to a region inside (the opening 6a side) of the range shown in Figures 2 and 3, and at most the entire surface inside the range shown in Figures 2 and 3 can be the inner frame surface 6b. The outer frame surface 6c may be expanded to a region outside (the outer contour side of the frame 6) of the range shown in Figures 2 and 3, and at most the entire surface outside the range shown in Figures 2 and 3 can be the outer frame surface 6c.

[0036] Furthermore, in the solid oxide fuel cell 100, the wettability of the end face 8 of the battery cell 10 may be made better than the wettability of the inner peripheral frame surface 6b. This increases the adhesive force of the glass seal material 7 to the end face 8, making it difficult for the glass seal material 7 to separate from the end face 8. This maintains the sealing ability of the end face 8.

[0037] The wettability of the end faces 8 of the battery cells 10 can be improved, for example, by applying an oxide coating to the metal support 2, as will be described in more detail below. Also, the end faces 8 having better wettability than the inner frame surface 6b may be achieved by adjusting the inner frame surface 6b to have a worse wettability than the end faces 8.

[0038] The above has described the configuration of the solid oxide fuel cell 100 according to the first embodiment. The solid oxide fuel cell 100 may be provided as a battery module in which a plurality of battery cells 10 are stacked.

[0039] Next, an example of a method for manufacturing the solid oxide fuel cell 100 according to this embodiment will be described. FIG.

[0040] (Step S1) Lamination of green sheets First, a green sheet laminate is prepared by laminating a green sheet for the metal support 2, a green sheet for the first electrode layer 3, a green sheet for the electrolyte layer 4, and a green sheet for the second electrode layer 5. The green sheet laminate can be formed, for example, by a tape casting method. Specifically, first, a slurry containing the raw materials of each layer included in the green sheet laminate is prepared. Then, each prepared slurry is formed into a sheet shape. This results in a green sheet for each layer. Furthermore, the obtained green sheets are laminated. This results in a green sheet laminate.

[0041] (Step S2) Cutting the green sheet laminate Subsequently, the green sheet laminate is cut into a desired shape as required.

[0042] (Step S3) Firing The green sheet laminate is then fired to obtain a fired laminate in which the metal support 2, the first electrode layer 3, the electrolyte layer 4, and the second electrode layer 5 are laminated in this order.

[0043] (Step S4) Supporting the anode catalyst and the cathode catalyst Next, the anode catalyst and the cathode catalyst are supported on the sintered laminate. For example, a catalyst solution containing each catalyst is prepared, and the prepared catalyst solution is impregnated into a specific position of the sintered laminate and heated. This allows the catalyst to be supported, and the battery cell 10 is formed. Note that the impregnation with the catalyst solution and heating may be performed multiple times to support a desired amount of catalyst.

[0044] (Step S5) Removal process Next, a portion of the second electrode layer 5 is removed from the outer periphery of the battery cell 10 to expose the electrolyte layer 4. The second electrode layer 5 can be removed chemically, for example, by etching with a solution (e.g., acid). Alternatively, the second electrode layer 5 may be removed by mechanical processing.

[0045] (Step S6) Frame welding Next, the battery cells 10 are placed on the frame 6. Then, the battery cells 10 and the frame 6 are joined by welding. The welding may be, for example, laser welding or brazing.

[0046] The frame 6 has previously been subjected to a wettability improvement treatment (smoothing treatment, oxide film formation treatment, material addition treatment) to improve the wettability of the inner frame surface 6b and / or a wettability reduction treatment (roughening treatment, oxide film removal treatment, material addition treatment) to reduce the wettability of the outer frame surface 6c (step S7).

[0047] (Step S8) Formation of glass sealant 7 Next, a glass sealant 7 is formed so as to cover the end face 8 of the battery cell 10. In this manner, a solid oxide fuel cell 100 having the structure shown in Figs.

[0048] For example, glass powder can be placed at the position where glass sealant 7 is to be formed and melted by heating to form the glass sealant 7. Alternatively, a binder resin with glass powder dispersed therein can be prepared, and this binder resin can be applied to a predetermined position of the battery cell 10 and fired to form the glass sealant 7. Alternatively, a green sheet containing glass powder can be placed at a predetermined position and fired to form the glass sealant 7.

[0049] <Second embodiment> Next, a description will be given of a second embodiment. In the second embodiment, the same components as those in the first embodiment are denoted by the same reference numerals and will not be described.

[0050] Fig. 5 is a schematic cross-sectional view of a solid oxide fuel cell 100 according to the second embodiment. As shown in Fig. 5, in the second embodiment, a glass sealant 7 permeates an end face 8 (metal support 2, first electrode layer 3) of a battery cell 10.

[0051] An anchor effect is created by the glass sealant 7 penetrating into the porous metal support 2. This holds the glass sealant 7 on the end face 8 of the battery cell 10 in place, preventing the formation of leak paths.

[0052] In the second embodiment, the surface of the metal support 2 is covered with an oxide material M, as shown in an enlarged view in FIG.

[0053] For example, by subjecting the metal support 2 to an oxidation treatment such as a high-temperature heat treatment, an oxide coating can be formed on the surface of the base material B constituting the metal support 2. Also, for example, an oxide coating can be formed on the base material B by a plating treatment or the like.

[0054] The adhesive strength between an oxide and glass is higher than that between a metal and glass. Therefore, by improving the adhesive strength with the glass sealant 7, it is possible to prevent the glass sealant 7 from flowing out from inside the metal support 2. Note that it is not essential that the surface of the metal support 2 is covered with the oxide material M.

[0055] It is preferable that the difference in thermal expansion coefficient between the metal support 2 and the oxide material M is within 10%. As an example, when the metal support 2 is ferritic stainless steel and the oxide material M is zirconium oxide, the difference in thermal expansion coefficient between them is within 10%.

[0056] By keeping the difference in thermal expansion coefficient between the metal support 2 and the oxide material M within 10%, it is possible to prevent cracks in the oxide coating due to thermal stress during operation of the solid oxide fuel cell 100. Therefore, the adhesive strength with the glass sealant 7 can be maintained.

[0057] <Third embodiment> Next, a description will be given of a third embodiment. In the third embodiment, the same components as those in the first embodiment are denoted by the same reference numerals and will not be described.

[0058] Fig. 6 is a schematic cross-sectional view of a solid oxide fuel cell 100 according to the third embodiment. As shown in an enlarged view in Fig. 6, in the third embodiment, the surface roughness of the inner circumferential frame surface 6b continuously increases with increasing distance from the battery cell 10.

[0059] The outer peripheral frame surface 6c has poorer wettability than the portion of the inner peripheral frame surface 6b that has the poorest wettability, that is, the outermost peripheral portion of the inner peripheral frame surface 6b. The wettability of the outer peripheral frame surface 6c may be adjusted by the above-mentioned wettability reduction treatment.

[0060] According to this, the force pushing the glass seal material 7 back toward the battery cell 10 increases as the glass seal material 7 is moved away from the battery cell 10. This makes it possible to prevent the glass seal material 7 from leaking out.

[0061] The configuration of the third embodiment may be combined with the configuration of the first embodiment, or may be combined with the configuration of the second embodiment.

[0062] The main configurations and effects of each embodiment will be described below.

[0063] The solid oxide fuel cell 100 includes a battery cell 10 having a porous metal support 2, a first electrode layer 3 laminated on the metal support 2, an electrolyte layer 4 laminated on the first electrode layer 3, and a second electrode layer 5 laminated on the electrolyte layer 4, and a frame 6 that holds the battery cell 10. An end face 8 of the battery cell 10 and the frame 6 are joined by a glass sealant 7. The frame 6 has an inner frame surface 6b in contact with the glass sealant 7 with better wettability than an outer frame surface 6c located outside the glass sealant 7.

[0064] With this, even if the solid oxide fuel cell 100 becomes hot and the glass sealant 7 softens, the glass sealant 7 is attracted to the inner frame surface 6b, which has better wettability than the outer frame surface 6c. In other words, the glass sealant 7 is prevented from flowing in a direction away from the battery cell 10. This prevents the glass sealant 7 from flowing and losing its sealing ability.

[0065] In the solid oxide fuel cell 100, the end faces 8 of the fuel cells 10 may have better wettability than the inner peripheral frame surface 6b.

[0066] This can increase the adhesive force of the glass seal material 7 to the end face 8, making it difficult for the glass seal material 7 to separate from the end face 8. As a result, the sealing performance of the end face 8 is maintained.

[0067] The glass sealant 7 may permeate the end faces 8 of the battery cells 10 .

[0068] An anchor effect is created by the glass sealant 7 penetrating into the porous metal support 2. This holds the glass sealant 7 on the end face 8 of the battery cell 10 in place, preventing the formation of leak paths.

[0069] The metal support 2 may be coated with an oxide material M.

[0070] The adhesive strength between an oxide and glass is greater than that between a metal and glass, and therefore the adhesive strength with the glass sealant 7 is improved, thereby preventing the glass sealant 7 from leaking out from inside the metal support 2.

[0071] The difference in thermal expansion coefficient between the metal support 2 and the oxide material M can be within 10%.

[0072] By keeping the difference in thermal expansion coefficient between the metal support 2 and the oxide material M within 10%, it is possible to prevent cracks in the oxide coating due to thermal stress during operation of the solid oxide fuel cell 100. Therefore, the adhesive strength with the glass sealant 7 can be maintained.

[0073] The surface roughness of the inner circumferential frame surface 6 b may be designed to continuously increase with increasing distance from the battery cells 10 .

[0074] According to this, the force pushing the glass seal material 7 back toward the battery cell 10 increases as the glass seal material 7 is moved away from the battery cell 10. This makes it possible to prevent the glass seal material 7 from leaking out.

[0075] The wettability of the outer peripheral frame surface 6c can be reduced by performing any one of the following processes: surface roughening, oxide film removal, and material addition.

[0076] By reducing the wettability of the outer peripheral frame surface 6c, a force acts to move the glass seal material 7 from the outer peripheral frame surface 6c, which has poor wettability, toward the inner peripheral frame surface 6b, which has good wettability, thereby preventing the glass seal material 7 from flowing out.

[0077] The wettability of the inner peripheral frame surface 6b can be improved by subjecting it to one of smoothing treatment, oxide layer formation treatment, and material addition treatment.

[0078] By improving the wettability of the inner frame surface 6b, a force acts to move the glass seal material 7 from the outer frame surface 6c, which has poor wettability, toward the inner frame surface 6b, which has good wettability, thereby preventing the glass seal material 7 from leaking out.

[0079] Although an embodiment of the present invention has been described above, the above embodiment merely illustrates one application example of the present invention, and is not intended to limit the technical scope of the present invention to the specific configuration of the above embodiment. [Explanation of symbols]

[0080] 100 Solid oxide fuel cell 10 Battery Cells 2 Metal support 3 First electrode layer 4 Electrolyte layer 5 Second electrode layer 6 Frames 6b Inner frame surface 6c Outer frame surface 7 Glass sealing material 8 End face M Oxide material

Claims

1. A porous metal support; A first electrode layer laminated on the metal support; an electrolyte layer laminated on the first electrode layer; A second electrode layer laminated on the electrolyte layer; A battery cell having A frame for holding the battery cells; Equipped with an end face of the battery cell and the frame are joined with a glass sealant; the frame has an inner peripheral frame surface that comes into contact with the glass sealant and has better wettability than an outer peripheral frame surface that is positioned outside the glass sealant; Solid oxide fuel cell.

2. 2. The solid oxide fuel cell according to claim 1, the end surface of the battery cell has better wettability than the inner peripheral frame surface; Solid oxide fuel cell.

3. 3. The solid oxide fuel cell according to claim 2, the glass sealant permeates the end surface of the battery cell; Solid oxide fuel cell.

4. The solid oxide fuel cell according to claim 3, The metal support is coated with an oxide material. Solid oxide fuel cell.

5. The solid oxide fuel cell according to claim 4, The difference in thermal expansion coefficient between the metal support and the oxide material is within 10%. Solid oxide fuel cell.

6. 2. The solid oxide fuel cell according to claim 1, the surface roughness of the inner circumferential frame surface continuously increases with increasing distance from the battery cell; Solid oxide fuel cell.

7. A method for producing the solid oxide fuel cell according to any one of claims 1 to 5, comprising the steps of: The outer peripheral frame surface is subjected to one of a roughening treatment, an oxide film removal treatment, and a material addition treatment to reduce the wettability of the outer peripheral frame surface. A method for producing a solid oxide fuel cell.

8. A method for producing the solid oxide fuel cell according to any one of claims 1 to 5, comprising the steps of: the inner frame surface is subjected to one of a smoothing treatment, an oxide layer forming treatment, and a material adding treatment, thereby improving the wettability of the inner frame surface; A method for producing a solid oxide fuel cell.

Citation Information

Patent Citations

  • Metal support solid oxide fuel cell and manufacturing method therefor

    JP2016207630A